Literary Lineages: Place, Translation, Method - de Mel, Neloufer; Patel, Geeta (My University, 2020)
This conversation between two scholars, Neloufer de Mel and Geeta Patel, will touch on how, in their interdisciplinary work, literature, translation, method and practice configure specific places and attachments in Sri Lanka and colonial, as well as contemporary India. It will draw on a literary archive that names and renarrates the cities of Jaffna, Lahore, Delhi and Mumbai, and will reflect on how questions and threads that materialize from translation as a theory and practice animate and vitalize their current work.
Keywords: Literary Lineages: Place, Translation, Method